TEACHING STUDENTS OF DIFFERENT LEVELS IN THE SAME CLASS - Maxliyo Gayratqizi Sobirova (Web of Journals Publishing, 2023)
This article presents ideas and reflections on the importance of teaching students of different abilities in the same classroom.
Keywords: Global, education, pedagogue, opportunity, culture, educational institutions, result, modern knowledge.